2013
DOI: 10.1177/0165551513514928
|View full text |Cite
|
Sign up to set email alerts
|

The power of words: A content analytical approach examining whether central bank speeches become financial news

Abstract: Few studies have examined the impact that central bank indirect intervention has on exchange rates. Efficient market theory predicts that new information within central bank communication will become a component of information used by currency traders. This study applies a novel methodology to examine whether information contained within Bank of Canada and the Reserve Bank of Australia communications does in fact get embedded within the information reported on the financial newswires. The primary data are spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…Masawi et al . () found that communication influences financial markets. Clarity, intensity, and internal consistency of communicated strategy has been shown to enhance IPO performance (Gao et al ., ).…”
Section: Strategic Integrity In the Context Of Corporate Restructuringmentioning
confidence: 99%
“…Masawi et al . () found that communication influences financial markets. Clarity, intensity, and internal consistency of communicated strategy has been shown to enhance IPO performance (Gao et al ., ).…”
Section: Strategic Integrity In the Context Of Corporate Restructuringmentioning
confidence: 99%
“…The first strand focuses on quantification through central bank or monetary policy transparency indices, measuring the degree of information disclosure (e.g., Geraats 2002Geraats , 2020Dincer and Eichengreen 2014;Dincer et al 2019Dincer et al , 2022. The second strand employs text mining techniques to identify policy concerns, decisions, and intentions (e.g., Masawi et al 2014;Hansen and McMahon 2016;Hansen et al 2018Hansen et al , 2019Warin and Sanger 2020;Küsters 2022). Our contribution relates to the second strand of rapidly growing empirical literature exploring central bank communication from a computational linguistics perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Informasi finansial dan reputasi perusahaan memiliki pengaruh yang kuat pada pasar saham (Cheung et al, 2020;Masawi et al, 2014;Naveed et al, 2020). Informasi khususnya pelaporan keuangan dan laporan analis finansial, diasumsikan dapat membentuk citra publik dan legitimasi perusahaan yang dapat mempengaruhi keputusan pembelian saham investor.…”
Section: Pendahuluanunclassified